Phage Therapy in Poland – a Centennial Journey to the First Ethically Approved Treatment Facility in Europe - Żaczek, Maciej; Weber-Dąbrowska, Beata; Międzybrodzki, Ryszard; Łusiak-Szelachowska, Marzanna; Górski, Andrzej (Frontiers in Microbiology, 2020)
Although phage discovery is an unquestionable merit of the English bacteriologist Frederick W. Twort and a Canadian-French microbiologist Félix d'Hérelle, who both discovered phage over 100 years ago, the Polish history of phage studies also dates back to those years. Contrary to the Western world, developing phage treatment in Poland has never been abandoned despite the country’s tense history marked by the Second World War and the communism era. Today, Poland takes a prominent and remarkable place in the phage research area. Furthermore, established in 2005, the Phage Therapy Unit at the Hirszfeld Institute of Immunology and Experimental Therapy in Wrocław, the first such center within European borders, has quickly become a model for other centers in the world facing the issue of wide-spread antibiotic resistance. This article constitutes an attempt to fill the gap in the scientific literature by providing a comprehensive summary of the long tradition of phage research in Poland.